DOES PRICE COMMODITY PALM OIL, RUBBER AND NON PERFORMING LOAN (NPL) AFFECT ON FINANCIAL PERFORMANCE - Tona Aurora Lubis; Asep Machpuddin; Agil Muharya (Management Department, Faculty of Economics and Business, Universitas Jambi, 2017)
The purpose of this study was to analyze the effect of commodity prices of rubber and palm oil, as well as Non Performing Loan (NPL) on financial performance (return on assets (ROA)) PT. Bank BRI Agro Tbk, either partially or simultaneously. Data used is secondary data, where data commodity prices of rubber and palm oil obtained from the Directorate General of Plantation while data on financial performance (return on assets (ROA)) obtained from the Annual report 2015 AGRO Bank BRI. The data were analyzed using multiple linear regression techniques. Results of statistical t test proves that partially price of rubber and palm oil does not significantly to influence of financial performance Bank BRI Agro Tbk, while NPL significant effect on financial performance Bank BRI Agro, Tbk. Results of statistical F test proves that simultaneously the price of rubber and palm oil as well as NPL has significant impact on financial performance. Bank BRI Agro, Tbk. The results of the study has implications for efforts to reduce the NPL ratio while maintaining the bank's function as intermediary (prudence) in extending credit, especially in the agricultural sector to reduce the high value of NPL (non-performing loans), considering the contribution of NPL sizeable influence on the financial performance of banks. Keywords: Price of palm oil, Price of rubber, Non Performing Loan (NPL), financial performance